All in the value: The impact of brand and social network relationships on the perceived value of customer endorsed Facebook advertising. (9th July 2018) - Ramadan, Zahy Bashir; Abosag, Ibrahim; Zabkar, Vesna
Abstract : Purpose: The purpose of this study is to test such effects on brands' relationships and the perceived value of advertising. Social advertising featuring endorsed brands has significantly grown in the past few years. Companies and social networking sites (SNSs) are hailing such types of advertising as being more credible to users as they feature their friends' indirect endorsements; however, the issue of friends' likability alongside the users' relationships with the actual SNS is seldom considered with regard to any potential negative/positive effects they might have on brands' relationships and the perceived value of advertising within SNSs. Design/methodology/approach: Taking a customer-centric approach and based on the social information processing theory, this study investigates the influence of friends' likability and similarity and users' relationships with the SNS (Facebook, FB) on brands' relationships and advertising value by using a Web-based survey. The total number of responses included in the analysis is 305. The data were analyzed using structural equation modeling and LISREL 8.8. Findings: The findings show that the overall user experience on FB is based on three key areas: socializing with friends, the relationship with the social network itself and the relationship with the advertised brands. These contribute to the perceived value of customer endorsed FB advertising. Research limitations/implications: The study discusses various significant implications for online platforms, brands and the success of online advertising within SNSs. Practical implications: The study provides managers with discussion on what they need to consider in relation to managing their brand relationship within SNSs and the importance of considering the role FB plays in such relationships. Originality/value: This study contributes to the existing literature by making the link between users' experiences/friendships within SNSs, their relationships with the SNS (FB) itself and their relationships with the advertised brand and examines how these three combined relationships impact the perceived value of the ads by users of FB.